2017
DOI: 10.1021/acs.orglett.7b01334
|View full text |Cite
|
Sign up to set email alerts
|

Radical Silyldifluoromethylation of Electron-Deficient Alkenes

Abstract: A reaction of bromo- and iododifluoromethyl-substituted silanes with electron-deficient alkenes in the presence of an N-heterocyclic carbene borane complex is described. The reaction is performed under irradiation with light-emitting diodes and proceeds via a radical chain mechanism. The resulting products, the functionalized silicon reagents, can undergo chemoselective transformations involving either the silyldifluoromethyl fragment or the functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…Modern synthetic methods are beginning to emerge for the preparation of complex substituted difluoroalkyl organosilanes, which will undergo addition to aldehydes. Examples include Dilman's radical‐mediated photochemical addition of a difluorosilyl radical to electron deficient alkenes to give complex carbonyl‐containing difluoroalkylsilane 46 , and Mikami's defluorinative difluorosilylation of lithium enolates using Me 3 SiCF 3 to give 48 . Both of these complex difluoroalkylsilanes undergo addition to aldehydes under similar fluoride‐mediated conditions to give difluoroalkyl alcohols 47 and 49 .…”
Section: Synthesis Of Difluoroketones By a Fluorinated‐building‐blmentioning
confidence: 99%
“…Modern synthetic methods are beginning to emerge for the preparation of complex substituted difluoroalkyl organosilanes, which will undergo addition to aldehydes. Examples include Dilman's radical‐mediated photochemical addition of a difluorosilyl radical to electron deficient alkenes to give complex carbonyl‐containing difluoroalkylsilane 46 , and Mikami's defluorinative difluorosilylation of lithium enolates using Me 3 SiCF 3 to give 48 . Both of these complex difluoroalkylsilanes undergo addition to aldehydes under similar fluoride‐mediated conditions to give difluoroalkyl alcohols 47 and 49 .…”
Section: Synthesis Of Difluoroketones By a Fluorinated‐building‐blmentioning
confidence: 99%
“…This silane is very sensitive to Lewis bases and accordingly it was used as a precursor of difluorocarbene, which can react with enol ethers [ 19 20 ] ( Scheme 1 ). We showed that this silane could be involved in the radical chain hydrofluoroalkylation of electron-deficient alkenes, using a boron hydride as a source of hydrogen [ 21 ]. We thought that silane 1 could couple with silyl enol ethers in the presence of a photocatalyst affording fluoroalkylation products.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, the Dilman group reported a radical silyldifluoromethylation of electron-deficient alkenes 237 assisted by an NHC•borane complex affording the silyldifluoroalkanes 239 in moderate to high yields (Scheme 97). 67 A wide range of electron-deficient alkenes with useful functional groups were suitable for this transformation. Control experiments with a light/dark sequence indicated a possible mechanism involving a radical chain pathway.…”
Section: Syn Thesismentioning
confidence: 99%